Identification of Genes Involved in Biogenesis of Outer Membrane Vesicles (OMVs) in Salmonella enterica Serovar Typhi - Nevermann, Jan; Silva, Andrés; Otero, Carolina; Oyarzún, Diego P.; Barrera, Boris; Gil, Fernando; Calderón, Iván L.; Fuentes, Juan A. (Frontiers in Microbiology, 2019)
Outer membrane vesicles (OMVs) are nano-sized proteoliposomes discharged from the cell envelope of Gram-negative bacteria. OMVs normally contain toxins, enzymes and other factors, and are used as vehicles in a process that has been considered a generalized, evolutionarily conserved delivery system among bacteria. Furthermore, OMVs can be used in biotechnological applications that require delivery of biomolecules, such as vaccines, remarking the importance of their study. Although it is known that Salmonella enterica serovar Typhi (S. Typhi), the etiological agent of typhoid fever in humans, delivers toxins (e.g., HlyE) via OMVs, there are no reports identifying genetic determinants of the OMV biogenesis in this serovar. In the present work, and with the aim to identify genes participating in OMV biogenesis in S. Typhi, we screened 15,000 random insertion mutants for increased HlyE secretion. We found 9 S. Typhi genes (generically called zzz genes) determining an increased HlyE secretion that were also involved in OMV biogenesis. The genes corresponded to ompA, nlpI, and tolR (envelope stability), rfaE and waaC (LPS synthesis), yipP (envC), mrcB (synthesis and remodeling of peptidoglycan), degS (stress sensor serine endopeptidase) and hns (global transcriptional regulator). We found that S. Typhi Δzzz mutants were prone to secrete periplasmic, functional proteins with a relatively good envelope integrity. In addition, we showed that zzz genes participate in OMV biogenesis, modulating different properties such as OMV size distribution, OMV yield and OMV protein cargo.